2001
DOI: 10.1515/zna-2001-0911
|View full text |Cite
|
Sign up to set email alerts
|

Conductivities of Room Temperature Molten Salts Containing AlCl3, Measured by a Computerized Direct Current Method

Abstract: The conductivities of the binary room-temperature molten salt systems AlCl3-yV-«-butylpyridinium chloride (BPC), AlCl3-l-ethyl-3-methylimidazolium chloride (EMIC) and AlCl3-benzyltriethylammonium chloride (BTEAC) have been measured at different temperatures and compositions by a d.c. fourprobes method.There is a maximum of the conductivity at 50 mol% A1C13 in the A1C13-BPC and A1C13-EMIC systems at 40 to 80 °C, their activation energies being relatively low (20.79 and 14.76 kJ/mol, respec tively). As to the A1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…The difference in E a values suggests that we may be probing different phenomena (on different timescales) between the two conductivity measurements. Nonetheless, these activation energies are consistent with previous reports for similar ILAs demonstrating Arrhenius behavior. ,,,,,, Overall, we have demonstrated that the voltammetric-based conductivity measurement can be performed across a range of different measurement parameters.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The difference in E a values suggests that we may be probing different phenomena (on different timescales) between the two conductivity measurements. Nonetheless, these activation energies are consistent with previous reports for similar ILAs demonstrating Arrhenius behavior. ,,,,,, Overall, we have demonstrated that the voltammetric-based conductivity measurement can be performed across a range of different measurement parameters.…”
Section: Resultssupporting
confidence: 91%
“…Nonetheless, these activation energies are consistent with previous reports for similar ILAs demonstrating Arrhenius behavior. 17,29,35,42,44,63,64 Overall, we have demonstrated that the voltammetric-based conductivity measurement can be performed across a range of different measurement parameters. Effect of the Lewis Acid:Base Ratio.…”
Section: ■ Results and Discussionmentioning
confidence: 77%
See 1 more Smart Citation